Optimization of automation: III. Development of optimization method for determining automation rate in nuclear power plants. (September 2016) - Lee, Seung Min; Kim, Jong Hyun; Kim, Man Cheol; Seong, Poong Hyun
Highlights: We propose an appropriate automation rate that enables the best human performance. We analyze the shortest working time considering Situation Awareness Recovery (SAR). The optimized automation rate is estimated by integrating the automation and ostracism rate estimation methods. The process to derive the optimized automation rate is demonstrated through case studies. Abstract: Automation has been introduced in various industries, including the nuclear field, because it is commonly believed that automation promises greater efficiency, lower workloads, and fewer operator errors through reducing operator errors and enhancing operator and system performance. However, the excessive introduction of automation has deteriorated operator performance due to the side effects of automation, which are referred to as Out-of-the-Loop (OOTL), and this is critical issue that must be resolved. Thus, in order to determine the optimal level of automation introduction that assures the best human operator performance, a quantitative method of optimizing the automation is proposed in this paper. In order to propose the optimization method for determining appropriate automation levels that enable the best human performance, the automation rate and ostracism rate, which are estimation methods that quantitatively analyze the positive and negative effects of automation, respectively, are integrated. The integration was conducted in order to derive the shortest working time through considering the concept of situation awareness recovery (SAR), which states that the automation rate with the shortest working time assures the best human performance. The process to derive the optimized automation rate is demonstrated through an emergency operation scenario-based case study. In this case study, four types of procedures are assumed through redesigning the original emergency operating procedure according to the introduced automation and ostracism levels. Using the derivation process, the optimized automation rate is estimated through integrating the automation rate and ostracism rate according to the decreasing rate of working time. The automation rate that induces the most decreased rate of working time is calculated, and it is explained that the estimated automation rate is the optimized automation rate that provides the best operator performance for the circumstances. It is expected that the proposed automation rate optimization method will be useful in introducing automation with assurance of the best human performance.